2021
DOI: 10.1038/s41398-021-01691-2
|View full text |Cite
|
Sign up to set email alerts
|

The sooner the better: clinical and neural correlates of impulsive choice in Tourette disorder

Abstract: Reward sensitivity has been suggested as one of the central pathophysiological mechanisms in Tourette disorder. However, the subjective valuation of a reward by introduction of delay has received little attention in Tourette disorder, even though it has been suggested as a trans-diagnostic feature of numerous neuropsychiatric disorders. We aimed to assess delay discounting in Tourette disorder and to identify its brain functional correlates. We evaluated delayed discounting and its brain functional correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Another fMRI study focused on decisional impulsivity by using a delay-discounting task involving choosing between a small immediate reward or a larger delayed reward. 64 While they found no abnormal decisions in patients in comparison to a group of healthy controls, the authors identified a subgroup of patients with higher impulsivity. This group was also characterized by a higher burden of impulse-control disorders and a higher level of general impulsivity.…”
Section: Resultsmentioning
confidence: 91%
“…Another fMRI study focused on decisional impulsivity by using a delay-discounting task involving choosing between a small immediate reward or a larger delayed reward. 64 While they found no abnormal decisions in patients in comparison to a group of healthy controls, the authors identified a subgroup of patients with higher impulsivity. This group was also characterized by a higher burden of impulse-control disorders and a higher level of general impulsivity.…”
Section: Resultsmentioning
confidence: 91%
“…We interpret this across-subject result to reflect a lack of delayed discounting in response to risk cues in MI choosers and an inversion of risk estimation between LI and MI choosers. [81][82][83] Similar to reward, we see hemispheric differences between impulsivity groups, where MI choosers have greater encoding of risk in the left hemisphere, whereas LI choosers have greater encoding of risk in the right hemisphere. As our subject cohort has drug-resistant epilepsy, the electrode contacts are placed based solely on clinical considerations.…”
Section: Risk Models and Encodingmentioning
confidence: 81%
“…We interpret this across-subject result to reflect a lack of delayed discounting in response to risk cues in MI choosers and an inversion of risk estimation between LI and MI choosers. 8183…”
Section: Discussionmentioning
confidence: 99%